Study of the disaster-causing mechanism and reinforcement measures for soft rock deformation and lining cracking - Shi, J. W.; Zhou, P. Y.; Li, X.; Fan, S. Y.; Zhou, Z. F.; Zhi, B.; Cheng, Y. (Frontiers in Earth Science, 2023)
The underground engineering construction is facing increasingly complex geological conditions and engineering challenges. In especial, surrounding rock deformation and secondary lining cracking seriously threaten the tunnel construction and operation safety. In view of the above problems, a natural gas pipeline tunnel crossing expansive mudstone strata with layered joints was taken as an example, the characteristics of surrounding rock deformation and lining cracking were analyzed through field investigation. Then, the disaster-causing mechanism and corresponding control measures were studied through laboratory test and numerical simulation, which was applied to actual construction. Meanwhile, the deformation and stress response of surrounding rock and tunnel structure were analyzed and discussed through monitoring and numerical data. The results showed that the vault settlement and horizontal convergence deformation of surrounding rock were 170.52 mm and 99.81 mm respectively under improved construction scheme, which were 64.69 mm and 54.74 mm lower than those under original construction scheme. The maximum surrounding rock stress was 430.26 kPa under improved construction scheme, which was reduced by 18.15%. The maximum axial force of steel arch frame was 33.02 kN, ensuring the stability of supporting structure and the safety of tunnel construction. Finally, the rationality and effectiveness of the reinforcement measures adopted was assessed.